Sedimentary and geochemical properties of sediment cores from the northern Barents Sea - Thaise Ricardo de Freitas; Silvia Hess; Paul E Renaud; Peter G Appleby; Elisabeth Alve (PANGAEA, 2025)
Here we present sediment core geochemistry, radiometric dating, and grain size data collected during the Nansen Legacy Paleo Cruise (2018) and the Seasonal Cruise Q1 (2021) onboard R/V Kronprins Haakon. Our aim was to extend previous assessments of the distribution of modern sediment properties and organic carbon accumulation along the northern Barents Sea continental margin. Sediment cores were collected from nine stations with a four-tube multi-corer in August 2018, with one additional site sampled with a boxcorer in March 2021. Elemental (C, N) and stable isotopic compositions (δ13C, δ15N) were analysed in different sections of a shelf-to-basin transect with distinct geomorphological, geochemical, and hydrographic features. We examined the recent temporal variation of these properties in radiometrically dated sediment cores covering the last century.